PENERAPAN PENDEKATAN CULTURALLY RESPONSIVE TEACHING BERBASIS MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PADA MATA PELAJARAN PENDIDIKAN PANCASILA DI KELAS 5 SDN 101766 BANDAR SETIA: Penelitian Tindakan Kelas - Alzani Ulfa; Samio; Siti Khayroiyah; Ismiati Ahya (STKIP Subang, 2025)
The low learning outcomes of fifth-grade students in the Pancasila education subject at SD Negeri 101766 Bandar Setia served as the background for this study. The problem was caused by a learning approach that did not accommodate the students’ cultural diversity and lacked active student engagement in the learning process. This study aimed to improve student learning outcomes through the implementation of a Culturally Responsive Teaching approach combined with the Problem Based Learning model. This research employed Classroom Action Research (CAR) conducted in two cycles involving 25 students as the research subjects. Each cycle consisted of planning, action, observation, and reflection stages. Data were collected through achievement tests, observations, questionnaires, and reflective journals. The results showed a significant improvement across all assessed aspects. The average student mastery increased from 44% in the pre-action phase to 68% in Cycle 1 and reached 92% in Cycle 2. Detailed mastery in Cycle 2 included 88% cognitive, 92% affective, and 96% psychomotor aspects. Thus, this approach proved effective in enhancing learning outcomes and holistically developing students’ character in accordance with Pancasila values.